A Rigid-Beam-Model for studying the dynamic behaviour of cantilever masonry walls. (October 2021) - Baraldi, Daniele; Milani, Gabriele; Sarhosis, Vasilis
Abstract: In this work, a simple and effective Rigid Beam Model recently introduced for studying the dynamic behaviour of ancient freestanding stone columns is extended to the case of cantilever unreinforced masonry walls, considered along their thickness and subjected to out-of-plane loading. Both monolithic and multi-block walls were investigated. The proposed model assumes each block of the wall as a rigid beam element and each interface as a node. By assuming no sliding along the interfaces and small displacements of blocks, rocking can be simulated by a bi or tri-linear moment rotation non-linear constitutive law. Different in geometry monolithic and multi-block masonry walls were developed in the numerical model and subjected to different in magnitude and frequency harmonic loading. Their response was compared against those from the literature and good agreement was found. From the analysis results, it was found that monolithic walls can overturn with acceleration magnitudes larger than their corresponding static load multipliers, if input frequency values increase. However, overturning accelerations of multi-block walls increase less rapidly for increasing input frequency with respect to the corresponding equivalent monolithic walls. Collapse mechanisms involving wall portions above the base were found in addition to traditional overturning ones with respect to the base. To ensure reproducibility of results, input and output files will be made publicly available.